Hubungan Tingkat Pengetahuan Petani dengan Tingkat Produktivitas Kopi Arabika di Kecamatan Kayu Aro Barat Kabupaten Kerinci - septika Resa Alena; Dedi Hermon (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This study aims to analyze the relationship between the level of knowledge of farmers and the level of productivity of arabica coffee in Kayu Aro Barat District, Kerinci Regency. This type of research is quantitative descriptive research. The population in this study were all arabica cofee farmers in Kayu Aro Barat District. Amounting to 153 peoples. The sample in this study was 60 respondents. The sampling technique used is Simple Random Sampling. Data collection techniques in this study are test instruments and questionnaires and hypothesis testing in this study using the product moment correlation formula. The results of this study indicate that there is a relationship between the level of knowledge of armers and the level of prductivity of arabica coffee. This is evidenced by calculations where rcount > rtable is 0,379 > 0,254. The relationship between these two variables is positive because the value of r is positive and is in the low category.